ABCG11 modulates cytokinin responses in Arabidopsis thaliana - Yang, Qianying; Zhang, Jie; Kojima, Mikiko; Takebayashi, Yumiko; Uragami, Takuya; Kiba, Takatoshi; Sakakibara, Hitoshi; Lee, Youngsook (Frontiers in Plant Science, 2022)
The Arabidopsis ABC transporter ABCG11 transports lipidic precursors of surface coating polymers at the plasma membrane of epidermal cells. Mutants in ABCG11 exhibit severe developmental defects, suggesting that ABCG11 might also participate in phytohormone-mediated development. Here, we report that ABCG11 is involved in cytokinin-mediated development. The roots of abcg11 mutant seedlings failed to respond to cytokinins and accumulated more cytokinins than wild-type roots. When grown under short-day conditions, abcg11 exhibited longer roots and shorter hypocotyls compared to wild type, similar to abcg14, a knockout mutant in a cytokinin transporter. Treatment with exogenous trans-zeatin, which inhibits primary root elongation in the wild type, enhanced abcg11 primary root elongation. It also increased the expression of cytokinin-responsive Arabidopsis response regulator (ARR) genes, and the signal of the TCS::GFP reporter in abcg11 roots compared to wild-type roots, suggesting that cytokinin signaling was enhanced in abcg11 roots. When we treated only the roots of abcg11 with trans-zeatin, their shoots showed lower ARR induction than the wild type. The abcg14 abcg11 double mutant did not have additional root phenotypes compared to abcg11. Together, these results suggest that ABCG11 is necessary for normal cytokinin-mediated root development, likely because it contributes to cytokinin transport, either directly or indirectly.